2007
DOI: 10.1103/physrevb.76.201401
|View full text |Cite
|
Sign up to set email alerts
|

Probing the electronic structure of bilayer graphene by Raman scattering

Abstract: The electronic structure of bilayer graphene is investigated from a resonant Raman study using different laser excitation energies. The values of the parameters of the Slonczewski-Weiss-McClure model for graphite are measured experimentally and some of them differ significantly from those reported previously for graphite, specially that associated with the difference of the effective mass of electrons and holes. The splitting of the two TO phonon branches in bilayer graphene is also obtained from the experimen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
320
3
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(375 citation statements)
references
References 21 publications
45
320
3
7
Order By: Relevance
“…Thus, there are five independent parameters in the Hamiltonian (16) of intrinsic bilayer graphene, namely γ 0 , γ 1 , γ 3 , γ 4 and ∆ ′ . The band structure predicted by the tight-binding model has been compared to observations from photoemission [16], Raman [76] and infrared spectroscopy [55,56,[78][79][80][81]. Parameter values determined by fitting to experiments are listed in Table I for bulk graphite [67], for bilayer graphene by Raman [76,77] and infrared [55,56,80] spectroscopy, and for a This parameter was not determined by the given experiment, the value quoted was taken from previous literature.…”
Section: Bilayer Graphenementioning
confidence: 99%
“…Thus, there are five independent parameters in the Hamiltonian (16) of intrinsic bilayer graphene, namely γ 0 , γ 1 , γ 3 , γ 4 and ∆ ′ . The band structure predicted by the tight-binding model has been compared to observations from photoemission [16], Raman [76] and infrared spectroscopy [55,56,[78][79][80][81]. Parameter values determined by fitting to experiments are listed in Table I for bulk graphite [67], for bilayer graphene by Raman [76,77] and infrared [55,56,80] spectroscopy, and for a This parameter was not determined by the given experiment, the value quoted was taken from previous literature.…”
Section: Bilayer Graphenementioning
confidence: 99%
“…The 2D band of multilayer graphene can be fitted with multiple peaks, due to the splitting of the electronic band structure of the multilayer material [20]. The electronic structure of bilayer graphene (BLG) has also been probed by resonant Raman scattering [21]. Electrical fi eld effect studies have revealed that electron/hole doping in graphene will affect the electron-phonon coupling, and hence the Raman frequency [22 24].…”
Section: Nano Researchmentioning
confidence: 99%
“…13 For bilayer graphene the parameters of the Slonzcewski-Weiss-McClure ͑SWMC͒ Hamiltonian have been fitted to reproduce double resonance Raman data. 21 A direct observation of the QP band structure is possible by ARPES, and a set of TB parameters has been fitted to the experimental ARPES data of graphene grown on SiC. 22 As a result they obtained a surprisingly large absolute value of the nearest-neighbor hopping parameter of 5.13 eV.…”
Section: Introductionmentioning
confidence: 99%